From migrants to citizens : membership in a changing world - Klusmeyer, Douglas B., 1957-; Aleinikoff, T. Alexander (Thomas Alexander), 1952- (Washington, D.C. : Carnegie Endowment for International Peace, 2000)
Citizenship policies are changing rapidly in the face of global migration trends and the inevitable ethnic and racial diversity that follows. The debates are fierce. What should the requirements of citizenship be' How can multi-ethnic states forge a collective identity around a common set of values, beliefs and practices' What are appropriate criteria for admission and rights and duties of citizens' This book includes nine case studies that investigate immigration and citizenship in Australia, the Baltic States, Canada, the European Union, Israel, Mexico, Russia, South Africa and the United States. This complete collection of essays scrutinizes the concrete rules and policies by which states administer citizenship, and highlights similarities and differences in their policies. From Migrants to Citizens, the only comprehensive guide to citizenship policies in these liberal-democratic and emerging states, will be an invaluable reference for scholars in law, political science, and citizenship theory. Policymakers and government officials involved in managing citizenship policy in the United States and abroad will find this an excellent, accessible overview of the critical dilemmas that multi-ethnic societies face as a result of migration and global interdependencies at the end of the twentieth century.
Citizenship in countries of immigration : introduction to part one / David A. Martin -- Citizenship and immigration in Australia / Gianni Zappal and Stephen Castles -- The dilemmas of Canadian citizenship law / Donald Galloway -- Between principles and politics : U.S. citizenship policy / T. Alexander Aleinikoff -- Citizenship in the aftermath of major political transformations : introduction to part two / Kathleen Newland -- Migration and admittance to citizenship in Russia / George Ginsburgs -- Post-apartheid citizenship in South Africa / Jonathan Klaaren -- The making of citizenship policy in the Baltic States -- Lowell W. Barrington -- Dual and supranational citizenship : limits to transnationalism : introduction to part three / Rainer Baubick -- Nationality in Mexico / Manuel Becerra Ramirez -- Citizenship of the European Union / Marco Martiniello -- Citizenship in Israel and Japan : introduction to part four / Aristide R. Zolberg -- Citizenship and membership in the Israeli polity / Ayelet Shachar -- Citizenship in Japan : legal practice and contemporary development / Chikako Kashiwazaki -- Conclusion--Managing membership : new trends in citizenship and nationality policy / Miriam Feldblum.
Includes bibliographical references and index.
Vendor-supplied metadata.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
JSTOR
Keywords: Citizenship; Emigration and immigration law; POLITICAL SCIENCE -- Political Freedom & Security -- Civil Rights; POLITICAL SCIENCE -- Political Freedom & Security -- Human Rights; Citizenship; Emigration and immigration law; Immigranten; Burgerschap; Nationaliteitsrecht; Overheidsbeleid